Peripheral and integral membrane binding of peptides characterized by time-dependent fluorescence shifts: focus on antimicrobial peptide LAH₄ - Macháň, Radek; Jurkiewicz, Piotr; Olżyńska, Agnieszka; Olšinová, Marie; Cebecauer, Marek; Marquette, Arnaud; Bechinger, Burkhard; Hof, Martin (Langmuir, 2014)
Positioning of peptides with respect to membranes is an important parameter for biological and biophysical studies using model systems. Our experiments using five different membrane peptides suggest that the time-dependent fluorescence shift (TDFS) of Laurdan can help when distinguishing between peripheral and integral membrane binding and can be a useful, novel tool for studying the impact of transmembrane peptides (TMP) on membrane organization under near-physiological conditions. This article focuses on LAH4, a model α-helical peptide with high antimicrobial and nucleic acid transfection efficiencies. The predominantly helical peptide has been shown to orient in supported model membranes parallel to the membrane surface at acidic and, in a transmembrane manner, at basic pH. Here we investigate its interaction with fully hydrated large unilamellar vesicles (LUVs) by TDFS and fluorescence correlation spectroscopy (FCS). TDFS shows that at acidic pH LAH4 does not influence the glycerol region while at basic pH it makes acyl groups at the glycerol level of the membrane less mobile. TDFS experiments with antimicrobial peptides alamethicin and magainin 2, which are known to assume transmembrane and peripheral orientations, respectively, prove that changes in acyl group mobility at the glycerol level correlate with the orientation of membrane-associated peptide molecules. Analogous experiments with the TMPs LW21 and LAT show similar effects on the mobility of those acyl groups as alamethicin and LAH4 at basic pH. FCS, on the same neutral lipid bilayer vesicles, shows that the peripheral binding mode of LAH4 is more efficient in bilayer permeation than the transmembrane mode. In both cases, the addition of LAH4 does not lead to vesicle disintegration. The influence of negatively charged lipids on the bilayer permeation is also addressed.
Keywords: kationické antimikrobiální peptidy; unilamelární lipozómy; Unilamellar Liposomes; alamethicin; Glycerol; Lipid Bilayers; Spectrometry, Fluorescence; Humans; glycerol; fluorescenční spektrometrie; Protein Conformation; lipidy; lidé; Alamethicin; magnetická rezonanční spektroskopie; Magainins; peptidy; časové faktory; Antimicrobial Cationic Peptides; Drug Design; Peptides; lipidové dvojvrstvy; racionální návrh léčiv; Hydrogen-Ion Concentration; Lipids; magaininy; Magnetic Resonance Spectroscopy; koncentrace vodíkových iontů; Time Factors; konformace proteinů